The Gap in the Fence: Austerity Cuts, Retrenchment and European Theatre’s Wake-up Call - Freeman, John (University of Bologna, 2013)
As the world well knows, austerity cuts in Europe mean that small-to-medium theatre companies are facing an uncertain future, to the extent that the golden age of funding is coming to an end. But has the theatre this funding has produced been golden in itself? And are Europeans turning a drama into a crisis when they use the term “austerity”? This paper puts forward the provocative argument that subsidy is as likely to suppress innovative theatre as it is to support it and that, perhaps, theatre functions best as an outlaw genre, free from public control masquerading as support.